Cemilan Snack Stik Dan Nugget Bayam Solusi Masalah Gizi Pada Anak Untuk Mencegah Stunting Di Desa Pucak Kab Maros - Fachrin, Suharni A.; A. Nurlinda; Baharuddin, Alfina (Window of Community Dedication Journal, 2023)
Stunting in children is closely related to nutritional problems. Spinach is one type of vegetable that is highly nutritious. Spinach can provide benefits to the health of the body from the nutritional content in it. Spinach is a vegetable that is easily obtained at a very affordable price. Variations of processed spinach into snacks are needed to increase the appetite of children who do not like vegetables, especially green vegetables. Spinach vegetables can improve nutritional nutrition in preventing stunting in children. The partner problems are: Spinach vegetables have a lot of nutritional content that is good for the body, and are still underutilized by farmers, especially housewives In terms of food diversification that is of economic value, there is still low public knowledge about diversifying spinach processing into advanced processed products, so an activity is needed that can increase public knowledge about various processed products that can be developed from spinach so that the economic value of spinach leaves can be increased. The results of the service showed that there was an increase in mirta's knowledge from the pre-test activity in the sufficient category (85%) while for the post-test it increased to 95%. There was an increase in partner attitudes from pre-test activities in the sufficient category (80%) while for the post test it increased to 95%. There was an increase in partner actions from pre-test activities in the sufficient category (85%) while for the post test it increased to 90%.